Construction of a cement–rebar nanoarchitecture for a solution‐processed and flexible film of a Bi2Te3/CNT hybrid toward low thermal conductivity and high thermoelectric performance. Issue 1 (3rd December 2021) - Chen, Zhijun; Lv, Haicai; Zhang, Qichun; Wang, Hanfu; Chen, Guangming
Abstract: Solution processability and flexibility still remain major challenges for many thermoelectric (TE) materials, including bismuth telluride (Bi2 Te3 ), a typical and commercially available TE material. Here, we report a new solution‐processed method to prepare a flexible film of a Bi2 Te3 /single‐walled carbon nanotube (SWCNT) hybrid, where the dissolved Bi2 Te3 ion precursors are mixed with dispersed SWCNTs in solution and recrystallized on the SWCNT surfaces to form a "cement–rebar"‐like architecture. The hybrid film shows an n‐type characteristic, with a stable Seebeck coefficient of −100.00 ± 1.69 μV K −1 in air. Furthermore, an extremely low in‐plane thermal conductivity of ∼0.33 W m −1 K −1 is achieved at 300 K, and the figure of merit (ZT) reaches 0.47 ± 0.02. In addition, the TE performance is independent of mechanical bending. The unique "cement–rebar"‐like architecture is believed to be responsible for the excellent TE performances and the high flexibility. The results provide a new avenue for the fabrication of solution‐processable and flexible TE hybrid films and will speed up the applications of flexible electronics and energy conversion. Abstract : A solution‐processed Bi2 Te3 /SWCNT (2 wt%) hybrid film shows a high figure of merit (ZT) of ∼0.47 with an extremely low thermal conductivity of ∼0.33 W m −1 K −1 at 300 K and the hybrid film shows excellent flexibility and high stability, showing promising potential for versatile applications, especially flexible and wearable electronics.